Comparative Evaluation of Fusobacterium and Leptotrichia among Patients with Oral Leukoplakia and Healthy Individuals - Senthil Kumar Balasubramanian; Suman Jhansi Lakshmi; J Anand Kumar; Keerthana Selvam; S Sam Ponraj Davidson; R Gomathi (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives: The present study attempts to evaluate and assess the presence of Fusobacterium, Leptotrichia, and Campylobacter among patients manifesting oral leukoplakia and healthy individuals. The aim is to compare variations in the presence of total microbiomes in the oral cavity of patients manifesting oral leukoplakia and healthy individuals. Methods: This study comprised 55 male subjects, 27 with a history of tobacco smoking (leukoplakia patients) and 28 healthy individuals (nonsmokers) within the age range of 30 years and above. Mucosal swabs were collected from the oral sites of the subjects, and the microbial counts were assessed in the laboratory. Comparative evaluation of Fusobacterium, Leptotrichia, and the total microbiome of oral leukoplakia patients and healthy individuals was statistically analyzed using SPSS version 22.0. Results: The culture analysis of the study subject samples indicated a higher value of total microbial flora count, Fusobacterium, and Leptotrichia when compared to that of control subjects. Conclusions: This study suggests Fusobacterium and Leptotrichia may have a major influence in the malignant transformation of leukoplakia.